Vitamin D and relationship with metabolic risk factors for cardiovascular disease in adult women - Pajuelo Ramírez, Jaime (2018)
Introduction. Vitamin D deficiency is considered a public health problem in other countries. Has been reported that this deficiency is related to the risk of developing metabolic diseases. Methods. Study descriptive, crosssectional design in 110 adult women of Lima Metropolitana. The Body Mass Index (MBI) was calculated to define the nutritional status. Blood levels of insulin, glucose, lipid profile and 25 (OH) D (vitamin D) were determined. It was calculated Homeostatic Model of Assessment Index (HOMA-I). Was calculated and to define insulin resistance (IR) a HOMA-I ≥ 2,7. For the deficiency of 25 (OH)-D, the cut-off point was 30 ng/mL for the intake of vitamin D a frequency of consumption was used. The identification of dyslipidemias was made as recommended by the Third Report of the National Cholesterol Education Program Results. In patients with vitamin D deficiency, the average age, BMI, insulin, glucose, HOMA-I, total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides were higher compared to patients with normal vitamin D dosage, finding difference statistically significant for BMI (p<0,03), insulin levels (p<0,01), HOMA-I (p<0,01), and triglycerides (p<0,01). In addition, vitamin D deficiency was determined in patients with insulin resistance with the presence of obesity and overweight as well as in patients with hypertriglyceridemia (p<0,05); the risk of having vitamin D deficiency was associated with insulin resistance (OR: 3,28, CI:1,3-8,3) and with hypertriglyceridemia (OR: 4,07, CI:1,8-9,3). Conclusions. The deficiency of vitamin D showed association with two variables that identify metabolic risk: insulin resistance and hypertriglyceridemia, in the study population, which could explain the possible relationship of this vitamin with cardiovascular diseases.